Class theatre (Journal of Parents and Teachers, 2014)
This article analyzes the pedagogical benefits that theatre has as a didactic resource in class. It gives some suggestions to work that field as a part of the integral formation of the students.
Keywords: education; theatre; school; students; formation; resource; didactic